Altered serum levels of proteins involved in beta‐amyloid clearance in the aftermath of the Kumamoto magnitude 7.3 earthquake: Neuroimaging / Normal brain aging. (7th December 2020) - Uchida, Kazuhiko; Sato, Tadashi; Tanaka, Motomi; Oniki, Kentaro; Saruwatari, Junji; Itai, Yaeko; Takahashi, Noriaki; Matsuda, Hiroshi; Osame, Mitsuhiro
Abstract: Background: Our previous studies revealed that apoA‐I, transthyretin, and complement component 3 (C3) in serum were associated with cognitive decline, and that atrophy of atrophy of the medial temporal structures was associated with decreased levels of apoA‐I 1, 2) . Increased risk of dementia was observed in the aftermath of disaster like earthquake and tsunami. The 2016 Kumamoto Earthquake, which was featured twice strong earthquakes of seismic intensity 7 and aftershock activities in the long period, produced house damaging and persistent and strong stress in people. In present study, we analyzed the levels of the blood‐based biomarker and hippocampal atrophy in the aftermath of the earthquake. Method: We obtained the data of serum biomarker levels and MRI imaging at every 6 month during the 3 years after the 2016 Kumamoto Earthquake and also those at 6 months before the earthquake. In total, 111 serum marker‐test results were obtained from 6 months before to 42 months after the earthquake. Atrophy of the medial temporal structures was measured by the semi‐quantified VSRAD score in about 1, 000 subjects. Result: Serum transthyretin and C3 levels were decreased at 6 months after the earthquake, and continue lower levels until 12 months. We calculated values of composite makers of these 3 proteins and determined cut‐off level which discriminated MCI from non‐demented control. The positive rate using cut‐off value before the earthquake was increased to 44% at 6 months, and it reduced to 10% at 18 months after the earthquake. Significant reduction of the hippocampal volume in male at 24 and 36 months was observed, on the other hand, there is no significant change in hippocampal volume in female. Interstingly, seum ApoA‐I levels were decreased in male and increased in female after the earthquake, and significant relationship between apoA‐I levels and hippocampal volume. Conclusion: Blood‐based biomarkers related to Aβ clearance might be useful to grasp cognitive decline prior to neuroimaging changes in progression of cognitive impairment. Resources: 1) Lui S, et al . Alzheimers Dement (Amst), published online Dec 18 (2018); 2) Uchida K, et al . Alzheimers Dement (Amst) 1:270‐280 (2015).